Implementation of Online Registration Applications in Vocational High Schools Using the QRCode Method - Asri (Yayasan Cendekiawan Digital Indonesia, 2024)
The development of information technology has had a significant impact and is applied in various areas of life, including the world of education. The aim of this service is to build and implement an information system that can increase speed and accuracy, as well as minimize errors in manual recording. The service methods used include interviews and literature studies, direct observation, and application design using the Waterfall method which includes needs analysis, system design, implementation, testing and maintenance. Thorough testing of the application is carried out to ensure the functionality, security, speed and reliability of the system. Training on the use of the application is held for teachers, administrative staff, and students to provide in-depth understanding and practical demonstrations. The test results show that the system can run well, while the user response is very satisfied with the online registration application and the training provided. The implementation of this QR code-based application is expected to increase operational efficiency and provide a better experience for prospective students and parents. This initiative is a real step in the digital transformation at SMKN 3 BONE, in line with the increasingly rapid development of information technology, as well as improving the quality of the registration and administration process at the school.